(untitled) (The Research of Medical Science Review, 2025)
Medical devices are either directly or indirectly associated with health care and patient treatment. The primary cause of hospital-acquired infections (HAIs) is the colonization of bacteria on medical equipment. On medical equipment, microorganisms such as bacteria and fungus exist in the form of biofilms, which enable their long-term survival. The most common bacteria found in medical devices linked to the most common HAIs, such as catheter-related infections, urinary tract infections, bloodstream surveillance infections, and skin and soft tissue infections, are S. aureus, E. coli, K. pneumoniae, P. aeruginosa, and Enterococcus spp. The risk of bacterial and fungal infections is increased when these microorganisms are present on hospital surfaces and medical equipment. Thus, it is essential that hospital and healthcare personnel are properly informed on the risk factors and preventative strategies for HAIs. In order improve awareness of the risk factors for common bacteria present and the diseases they might cause, the purpose of this study was to identify the bacterial isolates from the local hospital in Havelian based on their biochemical characteristics. Twenty-one samples were collected from hospital surfaces and medical devices, including three from hospital curtains, three from hospital sinks, five from equipment trays, five from indwelling devices such as drips and catheters, and five from patient bed linens. These samples were then taken to the laboratory for additional analysis. Following biochemical analysis, the most common bacterial species were Bacillus (29%), Staphylococcus aureus and Escherichia coli (19%), Pseudomonas, and Neisseria (14%), whereas Enterococcus (5%), which had the lowest count. The significance of this research contributes to an extensive understanding of the sources of infectious microorganisms in medical environments.